The Cost of Maintaining a Currency Board: The Case of Bulgaria - Manolova, Hristina; Vasilev, Aleksandar; Camous, Antoine (Journal of Mathematical Economics and Finance; Vol 11 No 1 (2025): JMEF, Volume XI, Issue 1(20), Summer 2025, 2025)
We investigate the cost of maintaining a currency board regime in Bulgaria by using two sources of monetary policy shocks. We further compare the results of two identification strategies. Following Corsetti, Duarte and Mann (2018), we use a one-year German bond yield in a recursive VAR to determine its effect on output, prices and consumption. Next, we use changes in IY EONIA rate around ECB policy announcements as a monetary shock that potentially captures more information and test it with local projections on output, prices and consumption. We repeat the tests for Germany and Spain and find that all three countries yield different results with the two instruments and identifications. Our conclusion is that the currency board is performing well, and Bulgaria is well financially integrated within the EU.